566. Tocilizumab: A Friend or a Foe in COVID-19 Management?. (31st December 2020) - Hernandez, Jarelys M; Jariwala, Ripal; Piccicacco, Nicholas; Aslam, Sadaf; Lakshmi, Seetha
Abstract: Background: The emergence of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has led to many proposed treatments for COVID-19 induced cytokine release syndrome (CRS). We aimed to investigate the treatment response of Tocilizumab (TZB), an Interleukin-6 (IL-6) inhibitor in this single center study. Methods: A retrospective chart review in COVID-19 patients was conducted from 03/18/20 - 05/20/20. Patients with PCR confirmed COVID-19 who received TZB were included. Variables included dose and timing of TZB, trend of acute phase reactants, time to improved oxygenation and defervescence, 30-day mortality, and hospital/intensive care unit (ICU) length of stay (LOS). Descriptive statistics were used. Results: Twelve patients received TZB at least once during the study period. Median patient age was 51.5 years (interquartile range (IQR), 34–87), and mean body weight of 109 kg (SD = 33.8). At time of admission, mean day of illness was 6.6 days (SD = 3.3) into their illness. All patients received a standardized TZB dose of 400 mg, and 2 patients received a second dose. Nine out of 11 patients (75%) had elevated median IL-6 baseline levels of 38.3 (IQR < 5- 96.22). The average CRS score was elevated at 3.3 at the time of TZB administration. All patients who received TZB were on supplemental oxygen, and 58% were mechanically ventilated. A decrease in oxygen requirement in 24 hours was seen in mechanically ventilated patients (71%) compared to those not on mechanical ventilation (20%). Median ICU days were 17.5 (IQR, 3–39), and median LOS days were 21.5 (IQR 8–46). All patients had sustained decreases in CRP post-TZB administration. Almost half of patients (42%) were treated for bacterial pneumonia post TZB and 3 (25%) patients were treated for herpes simplex virus (HSV) reactivation. Majority (92%) of patients received additional COVID-19 therapies such as hydroxychloroquine, convalescent plasma, or remdesivir. During the study period only one patient expired. Conclusion: Our findings suggest that TZB may have a role in mechanically ventilated patients in decreasing oxygen requirement. However larger randomized studies are needed to understand which patients would benefit the most. Our study also highlights secondary infections and HSV reactivation in TZB patients. Disclosures: All Authors : No reported disclosures